Studi Komparatif Menggunakan Metode Profit untuk Optimalisasi Penilaian PBB atas Jaringan Kabel Telekomunikasi Bawah Laut - Ismy Suha; Irwan Aribowo (Politeknik Keuangan Negara STAN, 2022)
The authors compare the results of Land and Building Tax (PBB) valuation on underwater telecommunications cable network property for the tax year 2021 based on an assessment using the currently regulated method and the profits method. This topic was chosen due to the authors' hypothesis that there is a potential loss of PBB as a result of related property being undervalued despite the rapid development of the telecommunications industry during the COVID-19 pandemic. The difference in market value realization generated between the two methods becomes the potential for PBB which is expected to be explored in the future.